International online survey of 1048 individuals with functional neurological disorder. (5th August 2021) - Butler, Matthew; Shipston‐Sharman, Oliver; Seynaeve, Mathieu; Bao, Jianan; Pick, Susannah; Bradley‐Westguard, Abigail; Ilola, Eveliina; Mildon, Bridget; Golder, Dawn; Rucker, James; Stone, Jon; Nicholson, Timothy
Abstract: Background and purpose: Functional neurological disorder (FND) is common, and symptoms can be severe. There have been no international large‐scale studies of patient experiences of FND. Methods: A patient questionnaire was created to assess FND patient characteristics, symptom comorbidities and illness perceptions. Respondents were recruited internationally through an open access questionnaire via social media and patient groups over a month‐long period. Results: In total, 1048 respondents from 16 countries participated. Mean age was 42 years (86% female). Median FND symptom duration was 5 years, and median time from first symptom to diagnosis was 2 years. Mean number of current symptoms (core FND and associated) was 9.9. Many respondents had associated symptoms, for example fatigue (93%), memory difficulties (80%) and headache (70%). Self‐reported psychiatric comorbidities were relatively common (depression, 43%; anxiety, 51%; panic, 20%; and post‐traumatic stress disorder, 22%). Most respondents reported that FND had multiple causes, including physical and psychological. Conclusions: This large survey adds further evidence that people with FND typically have high levels of multiple symptom comorbidity with resultant distress. It also supports the notion that associated physical symptoms are of particular clinical significance in FND patients. Dualistic ideas of FND were not supported by respondents, who generally preferred to conceptualize the disorder as one at the interface of mind and brain. The need for a broad approach to this poorly served patient group is highlighted. Potential selection and response biases due to distribution of the survey online, mostly via FND patient groups, are a key limitation. Abstract : A questionnaire to assess functional neurological disorder (FND) characteristics, symptom comorbidities and illness perceptions was completed by 1048 respondents with FND. The mean number of current symptoms (core FND and associated) was 9.9, and many respondents had associated symptoms such as fatigue (93%), memory difficulties (80%) and headache (70%). This large survey adds further evidence that people with FND typically have high levels of multiple symptom comorbidity with resultant distress.